The uses of Iraqi women for Facebook and innovation made from them (Journal of the College of Education for Women, 2018)
The problem of research is to identify the uses of Iraqi women for Facebook and the motives of these uses and the innovations that have been achieved from them, in view of the increasing role-played by social networking sites in the lives of individuals in general and women in particular.The research seeks to identify the following: Identify the extent to which Iraqi women use Facebook and the usage motives and innovations achieved by the interviewees When they using Facebook. This study belongs to the descriptive studies that are interested in monitoring the characteristics of a particular phenomenon to identify its characteristics and characteristics.This study adopted the survey methodology to test the hypotheses of the study and how Iraqi women use the Facebook. This approach is considered the most appropriate scientific curriculum for this study. The study society is composed of all users (women) of Facebook, different age groups, all levels of education and different economic and social levels.